2020
DOI: 10.3171/2020.9.focus20681
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in neurosurgical patients undergoing nonurgent surgery during the COVID-19 pandemic

Abstract: OBJECTIVEThe COVID-19 pandemic has forced many countries into lockdown and has led to the postponement of nonurgent neurosurgical procedures. Although stress has been investigated during this pandemic, there are no reports on anxiety in neurosurgical patients undergoing nonurgent surgical procedures.METHODSNeurosurgical patients admitted to hospitals in eastern Lombardy for nonurgent surgery after the lockdown prospectively completed a pre- and postoperative structured questionnaire. Recorded data included dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 57 publications
(48 reference statements)
5
21
1
Order By: Relevance
“…The Relative Variable Importance Measure (rel VIM) (Carpita and Vezzoli, 2012), (Doglietto et al, 2020b) and the Partial Dependence Plots (PDP) (Friedman, 2001) (Doglietto et al, 2020a) were extracted from the model for a better understanding of the relationship between outcome and covariates.…”
Section: Methodsmentioning
confidence: 99%
“…The Relative Variable Importance Measure (rel VIM) (Carpita and Vezzoli, 2012), (Doglietto et al, 2020b) and the Partial Dependence Plots (PDP) (Friedman, 2001) (Doglietto et al, 2020a) were extracted from the model for a better understanding of the relationship between outcome and covariates.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, 25% of the study population had the anxiety trait. This was comparable to the study done by Doglietto et al .,[ 7 ] among the neurosurgical patients posted for non-urgent surgery during the COVID-19 pandemic in Italy, where 18.9% of their study population had the anxiety trait. Further, 12% of the patients in our study population displayed anxiety due to general preoperative factors which was found to be lower as compared to a study done by Vadhanan et al .,[ 5 ] among preoperative patients in India, where the figure was 30%.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 7.1% of our study population expressed anxiety specifically due to COVID-19-related factors as compared to 30.3% in the study by Doglietto et al . [ 7 ] This study was conducted during the immediate post-lockdown phase in Lombardy which had been one of the epicentres of the COVID-19 pandemic in Italy. In comparison, our study was conducted at a time when restrictions had been eased, and the COVID-19 cases were markedly fewer.…”
Section: Discussionmentioning
confidence: 99%
“…After the appearance of the first cases of COVID-19 on 10 March 2020 in Turkey, there was no significant difference between patients undergoing OHC before the pandemic and after the pandemic when we evaluated preoperative anxiety levels and POCP rates of the preoperative anxiety levels. In Italy, where the course of the pandemic is intense, high preoperative anxiety levels were found in non-emergency neurosurgery patients during the COVID-19 pandemic [28]. This difference may be due to geographic location or different types of operations.…”
Section: Ta B L E 2 Comparison Of Anxiety Levels and Preoperative Pain Between Groupsmentioning
confidence: 99%